Oxidation and purification of carbon nanostructures - Osswald, Sebastian; Etzold, Bastian J.M. (CRC Press, 2017)
The oxidation of carbon materials has been explored for decades and has become a powerful route to alter the properties of carbonaceous materials, particularly coal and graphite. Until recently, the oxidation process had two main functions: (1) increasing surface area and porosity by removing carbon atoms from the surface (activation) and (2) formation of organic functional groups on the carbon surface (functionalization). With the rise of nanotechnology, however, researchers have recognized a third application of the oxidation process: (3) intelligent design and modification of carbon nanostructures, by utilizing the selectivity of oxidation toward specific structural elements at the nanoscale.
CRIS-Team Scopus Importer:2023-08-15